2018
DOI: 10.2147/clep.s174807
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in people with dementia, delirium, and unspecified cognitive impairment in the general hospital: prospective cohort study of 6,724 patients with 2 years follow-up

Abstract: PurposeCognitive impairment is common in older people admitted to hospital, but the outcomes are generally poorly understood, and previous research has shown inconsistent associations with mortality depending on the type of cognitive impairment examined and duration of follow-up. This study examines mortality in older people with any cognitive impairment during acute hospital admission.Patients and methodsProspective cohort of 6,724 people aged ≥65 years with a structured cognitive assessment on acute admissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 35 publications
1
36
0
1
Order By: Relevance
“…Although a number of epidemiological studies have reported on a cognitive impairment-mortality relationship 3,7 , most of them concerned the association of cognitive impairment and mortality risk of elders in high-income contries [8][9][10][11][12] . In upper-middle income countries such as China, several studies have indicated that baseline cognitive impairment increases the risk of all-cause mortality 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of epidemiological studies have reported on a cognitive impairment-mortality relationship 3,7 , most of them concerned the association of cognitive impairment and mortality risk of elders in high-income contries [8][9][10][11][12] . In upper-middle income countries such as China, several studies have indicated that baseline cognitive impairment increases the risk of all-cause mortality 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…There is no previous reporting on associations between antidementia treatment and mortality after admission in this high-risk population of in-patients. People with dementia experience poor outcomes after hospitalization, with higher mortality than people with no dementia [27] , [28] . The present study shows for the first time that treatment with antidementia drugs is associated with reduced mortality in the population with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Many people with dementia are admitted to care homes from the acute hospital [26] . In the acute hospital setting, people with dementia have poor outcomes; they have longer hospital stays [27] , an increased risk of not returning home [26] , and high mortality [28] .…”
Section: Introductionmentioning
confidence: 99%
“…Eine systematische Literaturübersicht gibt folgende Variablen für einen schlechten Outcome an: Länge des Delirs, motorisch hypoaktiver Subtyp, Schwere des Delirs, vorbestehende psychiatrische Erkrankungen wie Demenz und Depression [14]. In der Literatur gibt es Hinweise, dass Spitalspatienten ohne Demenz, die ein Delir entwickeln, schwerer erkrankt sind als diejenigen mit vorbestehenden Hirnpathologien [15]. Allerdings zeigten van Roessel et al [16] Die in diesem Artikel enthaltenen Bilder und sonstiges Drittmaterial unterliegen ebenfalls der genannten Creative Commons Lizenz, sofern sich aus der Abbildungslegende nichts anderes ergibt.…”
Section: K Original Articleunclassified